Effects of aging on ocular vestibular-evoked myogenic potential using ER-3A insert earphone and B81 bone vibrator - Xu, Zhuo; Wang, Zhilin; Zhong, Bo; Wang, Minjiao; Fan, Xiaoqin; Ren, Cuncun; Qi, Meihao; Lin, Ying; Zha, Dingjun (Frontiers in Neurology, 2022)
Purpose: Aging is a process associated with degeneration and dysfunction of peripheral vestibular system or apparatus. This study aimed to investigate the influence of age on ocular vestibular-evoked myogenic potential (oVEMP) response rates and recording parameters using the B81 bone vibrator and compare them with air conduction stimuli (ACS) oVEMP response characteristics. Methods: In 60 healthy participants aged 10-71 years (mean age 39.9; 29 male participants), the oVEMP response was elicited using a B81 bone vibrator and an ER-3A insert earphone. The effects of age and stimulus on oVEMP response rates and recording parameters were evaluated. Results: Response rates and amplitudes declined with aging using either ACS or Bone-conducted vibration (BCV) stimulation, particularly in individuals over 60 years of age, whereas thresholds increased and N1 latencies were prolonged. BCV showed fewer risks of absent oVEMP response than ACS (p = 0.002). BCV acquired higher amplitudes (p < 0.001), lower thresholds, and shorter N1 and P1 latencies (all p < 0.001) than ACS. Conclusions: The absence of an oVEMP response may be attributed to aging rather than a concurrent vestibular disorder. B81-BCV likely produces higher mechanical drives to the vestibular hair cells at safer and non-traumatic levels compared with ACS, and therefore may be more likely to evoke a response in the elderly cohort, whose vestibular functional and mechanical sensitivity has declined. Thus, B81-BCV stimulation is more effective and safer to elicit oVEMPs, and it should be recommended when ACS fails in the clinic, particularly in the elderly population.